Dishabituation of the Tritonia Escape Swim - Mongeluzi, Donna L. (Cold Spring Harbor Laboratory Press, 2000)
When repeatedly elicited, the oscillatory escape swim of the marine mollusc Tritonia diomedea undergoes habituation of the number of cycles per swim. Although similar in most respects to habituation observed in vertebrates and other invertebrates, one key feature, dishabituation, has been surprisingly difficult to demonstrate. Here we evaluate the hypothesis that this is due to interference from short-term sensitization, which is manifested as a reduction in swim onset latency, that occurs simultaneously during habituation training. Robust dishabituation was obtained using a multisession habituation protocol designed to allow this sensitization to dissipate before the dishabituatory stimulus was applied. These results extend the similarity of habituation in Tritonia to that described in other species, strengthening the usefulness of this preparation as a model system for studies of the cellular basis of habituation.